Parallel fiber and climbing fiber responses in rat cerebellar cortical neurons in vivo - Jirenhed, Dan-Anders; Bengtsson, Fredrik; Jörntell, Henrik (Frontiers in Systems Neuroscience, 2013)
Over the last few years we have seen a rapidly increased interest in the functions of the inhibitory interneurons of the cerebellar cortex. However, we still have very limited knowledge about their physiological properties in vivo. The present study provides the first description of their spontaneous firing properties and their responses to synaptic inputs under non-anesthetized conditions in the decerebrated rat in vivo. We describe the spike responses of molecular layer interneurons in the hemispheric crus1/crus2 region and compare them with those of Purkinje cells and Golgi cells, both with respect to spontaneous activity and responses evoked by direct electrical stimulation of parallel fibers and climbing fibers. In agreement with previous findings in the cat, we found that the climbing fiber responses in the interneurons consisted of relatively long lasting excitatory modulations of the spike firing. In contrast, activation of parallel fibers induced rapid but short-lasting excitatory spike responses in all types of neurons. We also explored parallel fiber input plasticity in the short-term (10 min) using combinations of parallel fiber and climbing fiber stimulation. With regard to in vivo recordings from cerebellar cortical neurons in the rat, the data presented here provide the first demonstration that parallel fiber input to Purkinje cells can be potentiated using parallel fiber burst stimulation and they suggest that parallel fiber burst stimulation combined with climbing fiber input may lead to potentiation of PF inputs in MLIs. We conclude that the basic responsive properties of the cerebellar cortical neurons in the rat in vivo are similar to those observed in the cat and also that it is likely that similar mechanisms of parallel fiber input plasticity apply.